ANALISIS PENDAPATAN DITINJAU MELALUI AKSES MODAL, PERSAINGAN USAHA DAN KUALITAS LAYANAN: Studi Kasus UMKM Sektor Kuliner di Kabupaten Nganjuk - Rahayu, Dwi Puji; Mahendra, Prasetya Tri; Ananda, Lala Dwipa (Media Mahardhika, 2025)
The purpose of this study is to investigate how the revenue of MSMEs in the culinary sector in Nganjuk Regency is impacted by capital access, business competition, and service quality. The study used a survey-based quantitative methodology. Out of the 1,834 culinary MSMEs in Nganjuk Regency, 328 MSME owners were chosen to participate in the survey. The Slovin formula with a 5% margin of error was used to get the sample size. Questionnaires were used to gather data, and statistical software was used for analysis. With a significance value of 0.000, the results showed that capital access (X1) significantly and favorably affected MSME income. With a significance value of 0.000, business competition (X2) was also found to have a positive and significant influence. Additionally, with a significance value of 0.000, service quality (X3) also showed a positive and substantial relationship on MSME income. The income of culinary MSMEs in Nganjuk Regency was significantly impacted by capital access, business competitiveness, and service quality all at the same time, as evidenced by an F-count value of 187.629 that was higher than the F-table value of 2.63 and had a significance value of 0.000. These results imply that raising the revenue of MSMEs in the culinary industry mostly depends on the availability of funding, the capacity to adjust to market competition, and the dedication to providing top-notch service.